2019
DOI: 10.33545/gynae.2019.v3.i6b.393
|View full text |Cite
|
Sign up to set email alerts
|

Study of etiopathology and risk factors of antepartum haemorrhage in a tertiary care center

Abstract: Background: Antepartum hemorrhage (APH) is an obstetrical emergency and is one of the leading causes of maternal and perinatal mortality and morbidity. Incidence varies from 2-5% of all deliveries. It contributes to 15-20% of all maternal deaths in India. Such obstetric emergency if handled carefully with identification of risk factors and timely management of cases can reduce chances of maternal and perinatal complications. Methods: The present study is an observational ambidirectional study focusing on antep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study conducted by Ayushma J et al 12 found 21% of women with APH had prior history of caesarean section in their study group. In another study reported by Patvekar M et al, 10 17.3% and 34.7% of women with placenta praevia had a past history of caesarean section and abortion with curettage respectively. Their study findings were quite similar to our study finding.…”
Section: Discussionmentioning
confidence: 85%
“…A study conducted by Ayushma J et al 12 found 21% of women with APH had prior history of caesarean section in their study group. In another study reported by Patvekar M et al, 10 17.3% and 34.7% of women with placenta praevia had a past history of caesarean section and abortion with curettage respectively. Their study findings were quite similar to our study finding.…”
Section: Discussionmentioning
confidence: 85%